Improving Concept Understanding with Problem-Based Learning: Action Research at State Elementary School 106218 Pematang Toba - Arifah; Nurhabibi; Sofia, Nida Aya (Journal of Indonesian Primary School, 2024)
This study aims to improve student learning outcomes in Islamic religious education learning by using the problem based learning model. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data for this study were obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics. The results of the study indicate that the problem based learning model can improve student learning outcomes in Islamic religious education learning. Thus, the use of the problem based learning model can be used as an alternative to improve student learning outcomes in Islamic religious education learning.